Can the Sutherlandia herb or resistance exercise reverse the stress inducing effects of a mild-intermittent stress procedure - Neethling, Ian Garth (Stellenbosch : University of Stellenbosch, 2006)
Thesis (MSc (Physiological Sciences))--University of Stellenbosch, 2006.